O conceito de independência e dependência linear e os registros de representação semiótica nos livros didáticos de Álgebra Linear - Grande, André Lúcio (2006)
This research aims to investigate which semiotic representation registers are most used in Linear Algebra textbooks in the presentation and study of the topic linear independence. The mathematics textbook is a resource much used by the teachers in its work. They present many representation registers, which can to be analyzed qualitatively to assess their potential contribution to the teaching-learning process. To this end, five Linear Algebra textbooks were selected for an analysis which involved the diagnosis of the representation registers used in the definition of linear independence, as well as the examples and exercises proposed for its study. The theory used in the analysis of these textbooks was Raymond Duval´s theory of Registers of Semiotic Representation, which highlights the importance of changes between registers in the learning of mathematical objects. In each textbooks, the registers present were classified and analyzed, along with the possible transformations of registers as carried out in the resolution of the examples and considered exercises. As result, scarcity of the use of some registers of representation it was evidenced in the chapters that approach the slight knowledge of independence and linear dependence, as for example, the geometric one to determine if a set of vectors is linearly independent or not, and the register of the natural language, in the resolution of examples and considered exercises that involve demonstrations. The analysis also indicated a lack of attention to conversions between registers in the examples and proposed exercises of analyzed textbooks